1999
DOI: 10.1136/vr.144.16.433
|View full text |Cite
|
Sign up to set email alerts
|

A study of the aetiology of pseudopregnancy in the bitch and the effect of cabergoline therapy

Abstract: Thirty-two permanently pseudopregnant bitches were treated with the anti-prolactin drug cabergoline. They had all been ovariohysterectomised up to five months after their last season, in some cases over two years previously, when most were reported as showing no signs of the condition. The clinical signs were mainly behavioural, the majority being aggressive, and a small number were lactating. The efficiency of the cabergoline therapy was classified by the owners as 'excellent' or 'good' in 50 per cent of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 5 publications
(17 reference statements)
1
16
0
Order By: Relevance
“…Thus, in humans glycosylated PRL (G-PRL) has been reported to be up to 20, 32 and 50% in plasma in different studies [2,4,16] while in the same biologic fluid from rats it was reported to be 60% [1]. The biological activity of G-PRL in some of the classi- not detected significant differences in PRL levels between overt and covert PSPT bitches [11,12,15,20,22]. Indeed, a universal serum PRL threshold for triggering pseudopregnancy in the bitch is unlikely to exist.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, in humans glycosylated PRL (G-PRL) has been reported to be up to 20, 32 and 50% in plasma in different studies [2,4,16] while in the same biologic fluid from rats it was reported to be 60% [1]. The biological activity of G-PRL in some of the classi- not detected significant differences in PRL levels between overt and covert PSPT bitches [11,12,15,20,22]. Indeed, a universal serum PRL threshold for triggering pseudopregnancy in the bitch is unlikely to exist.…”
Section: Discussionmentioning
confidence: 95%
“…Although, most of the above results suggest that increased PRL concentrations are responsible for overt PSC, a recent study showed no signi®cant dierences in mean serum PRL levels between PSPT and non-PSPT bitches during 13 weeks in 28 Labrador Retrievers (Lawler et al 1999). A lack of signi®cant dierence in PRL levels between surgery-induced PSPT and non-PSPT animals has also been reported (Homann et al 1992;, and an overlap of PRL serum levels between PSPT and non-PSPT bitches post spaying (Harvey et al 1999). High PRL levels do not seem to be necessary for the maintenance of PSP as suggested by a report of low PRL levels in two spayed PSPT bitches (Harvey et al 1997).…”
Section: Aetiophysiologymentioning
confidence: 82%
“…Although it was once normal in wild dogs, PSC has now become a clinical problem in most domestic bitches bred as pets. PSC is relatively easy to diagnose and treatment with dopaminergic agonists have greatly helped in treating this syndrome (Arbeiter et al 1988;Harvey et al 1997Harvey et al , 1999Gobello et al 2001b). Although some of them have some side-eects, they are transient and can usually be managed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise aetiology of clinical pseudopregnancy is still poorly understood, but is reported to be linked with the exposure and decline of plasma progesterone, high plasma prolactin concentrations, an increased tissue sensitivity to prolactin, or the existence of molecular variants of prolactin with varying bioactivities [ 3 6 , 8 , 11 – 14 , 16 , 19 ]. Based on clinical studies on pseudopregnancy in dogs, the estimated incidence of clinical pseudopregnancy can be as high as 50–75% in certain breeds (e.g.…”
Section: Introductionmentioning
confidence: 99%